Generation of induced pluripotent stem cell line, NCHi027-A, from a female child with Posterior Cloaca (Type B) - Cintia E. Gomez Limia; Karunya Albert; Chaitrali Atre; Kusum Basnet; Darria L. Streeter; Nathalia G. Amado; Linda A. Baker (Stem Cell Research)
Cloaca is an ultra-rare severe anorectal malformation in females where the gastrointestinal, genital, and urologic systems converge. Posterior Cloaca (Type B) is an extremely rare specific variant, where the urogenital sinus opens just anterior to the anus. NCHi027-A is an iPSC line derived from skin fibroblasts of a 4 year and 8-month-old female with Posterior Cloaca (Type B) using Sendai Virus reprogramming. This iPSC line shows typical iPSC morphology, has normal karyotype, expresses pluripotency markers, and can be differentiated into three germ layers.